miRNA regulation of the Akt/mTOR pathway in oral squamous cell carcinoma: a focused review - Shazia Fathima Jaffer Hussain; Mohammad Fareed; Mohmed Isaqali Karobari (Discover Oncology)
Abstract Oral squamous cell carcinoma (OSCC) contributes significantly to global cancer mortality, characterized by a progression from hyperplasia to invasive cancer through a series of genetic and epigenetic alterations. Central to this progression is the Akt/mTOR signaling pathway, which regulates cell proliferation and survival. This review examines the role of microRNAs (miRNAs) in modulating the Akt/mTOR pathway and their implications for OSCC. The Akt/mTOR pathway, activated by receptor tyrosine kinases and involving the PI3K/AKT/mTOR complexes, is crucial for tumor cell growth and metabolism. Dysregulation of this pathway is frequently observed in OSCC, leading to increased proliferation, survival, and metastasis. miRNAs, such as miR-21, miR-99, and miR-145, play significant roles in regulating this pathway by influencing key components like Akt and mTOR. These miRNAs can act as oncogenes or tumor suppressors, affecting cancer progression and response to therapy. The review highlights the potential of targeting miRNAs for OSCC treatment, including strategies to restore normal miRNA levels or inhibit aberrant miRNAs. Such targeted therapies offer promise for improving treatment outcomes and overcoming drug resistance in OSCC. Graphical abstract